By their blood Christian martyres from the twentieth century and beyond - Hefley, James C.; Hefley, Marti (Grand Rapids, MI Baker, 2004)
Includes index.
Includes Auca 5 (p.316-353), Mr and Mrs Gabriel Contessee (Swiss Brethren, missionaries to Laos, p.103-4), Stan Dale (p.139), Graham Stains, Philip and Timothy (p.119)
Keywords: Christian martyrs -- 20th century